2022
DOI: 10.3748/wjg.v28.i24.2667
|View full text |Cite
|
Sign up to set email alerts
|

Rebuilding trust in proton pump inhibitor therapy

Abstract: Introduction of proton pump inhibitor (PPI) therapy into clinical practice has revolutionized treatment approach to acid-related diseases. With its clinical success came a widespread use of PPI therapy. Subsequently, several studies found that PPIs were oftentimes overprescribed in primary care and emergency setting, likely attributed to seemingly low side-effect profile and physicians having low threshold to initiate therapy. However, now there is a growing concern over PPI side-effect profile among both pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 75 publications
(101 reference statements)
0
13
0
Order By: Relevance
“…This should be combined with compliance with counseling on lifestyle changes [ 62 ], with weight loss potentially reducing PPI doses [ 22 ]. Overall, optimal dosing of PPIs combined with lifestyle management appears to be the most effective and cost-effective approach to managing patients with GERD where lifestyle changes are insufficient [ 1 , 5 , 20 , 44 ].…”
Section: Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…This should be combined with compliance with counseling on lifestyle changes [ 62 ], with weight loss potentially reducing PPI doses [ 22 ]. Overall, optimal dosing of PPIs combined with lifestyle management appears to be the most effective and cost-effective approach to managing patients with GERD where lifestyle changes are insufficient [ 1 , 5 , 20 , 44 ].…”
Section: Reviewmentioning
confidence: 99%
“…With PPIs firmly established as a first-line pharmacologic treatment for patients with GERD [ 1 , 5 , 20 , 44 , 47 ], which PPI to prescribe should be based on key issues, including their effectiveness, safety, and cost-effectiveness as there can be appreciable cost variations between the different PPIs [ 55 ]. In their review, Graham and Tansel (2018) and others have concluded that all PPIs are functionally equivalent [ 55 , 78 ].…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations